Meningkatkan Kualitas Lahan dengan Aplikasi Biochar Arang Sekam dan Pupuk Hayati pada Budidaya Jagung Musim Tanam III di Kabupaten Gunungkidul - Damasus Riyanto; Sukristiyonubowo Sukristiyonubowo; Sugeng Widodo (Seminar Nasional Lahan Suboptimal, 2019)
Riyanto D, Sukristiyonubowo S, Widodo S. 2019. Improving land quality by application of biochar and biofertility in corn cultivation of planting season III on Gunungkidul Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 400-408. Palembang: Unsri Press. Managing land resources and improving soil quality are currently urgent and very important for the continuation of future generations. Improvements in the quality of rainfed rice fields can be done, among others, by the application of biofertilizers and biochar. Biofertilizer is a group of living organisms whose activities can improve soil fertility. Biochar is a solid material obtained from the carbonization process of a biomass of agricultural or plantation waste. Biochar is a porous, high-carbon solid substance of more than 50%. The assessment of application biological fertilizers and biochar were carried out in Polaman, Wareng village, Wonosari district-Gunungkidul. The time of implementation in planting season III (June-September 2018) with the treatment as stated: (A) Control (without biological fertilizer and biochar) + 100% chemical fertilizer according to recommendation (325 kg/ha Urea, Phonska NPK 300 kg/ha), (B) Application of Biofertilizer (Agrofit) 400 g/ha, without biochar + 100% chemical fertilizer (C) Application of Biofertilizer (Agrofi), without biochar and 75% chemical fertilizer according to recommendation, (D) Application of rice husk biochar 2.0 tons/ha, + Agrofit biofertilizers and 100% chemical fertilizer (E) Application of Biofertilizers (Agrofit), and biochar 2 tons/ha + 75% chemical fertilizer. Each treatment was repeated 4 times. Irrigation utilizes were used 2 existing borehole wells and support by submersible pumps which are carried out in rotation on each cooperator farmer's land. The discharge of water in its well is 2.5 liters/second. The observation of maize growth plants at 20 DAP and 40  DAP and 60 DAP were shown that the treatmen B and D was the highest result in corn plant height and the amount of leaves compare to the others. While the yield of shelled corn showed that the combination of treatment with biochar application 2 tons/ha and agrofit biofertilizers+75% chemical fertilizer and application of biochar 2 tons/ha and 400 g/ha agrofit + 100% chemical fertilizer recommendation shows that the results are not significantly different, so it can be recommended that application biological fertilizers and biochar be able to save 25% chemical fertilizer. This treatment shown  that was better results than control (farmer treatment) and treatment only giving biochar or biological fertilizers in single application.Keywords: biological fertilizers, biochar, corn productivity, land quality, rainfed rice fields